Peran Pembelajaran PAI dalam Membentuk Karakter Santri di Pesantren Baiturrahmi Sidap-dap Simanosor - Marpaung, Ernidawati; Setiawan, Hasrian (EL-EMIR Institute, 2025)
Character development through education is one of the main goals of the national education system, especially in Islamic boarding schools (pesantren). Pesantren Baiturrahmi, as a traditional and modern Islamic educational institution, places Islamic Religious Education (IRE) at the core of developing students' (santri) personalities. This article explores in greater depth the role and effectiveness of IRE learning in shaping the character of students at Pesantren Baiturrahmi, highlighting the methods, approaches, challenges, and evaluation of the program’s success. The research was conducted through literature studies, observation, and interviews with pesantren administrators and students. The results of this study show that Islamic Religious Education at Pesantren Baiturrahmi plays a strategic role in shaping the students’ character holistically. Through an integrative curriculum, varied teaching methods, value habituation, and intensive supervision, the pesantren is able to produce students who are knowledgeable, have noble character, and are ready to contribute positively to society. The existing challenges must be addressed with innovation and cross-sector collaboration to ensure that pesantren remain relevant and excel in shaping the character of the nation's future generations.